2022
DOI: 10.1021/acsptsci.2c00077
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cannabis in Infused Consumer Products and Their Residues on Skin

Abstract: Cannabis consumer products are a $4.6 billion industry in the U.S. that is projected to exceed $14 billion by 2025. Despite an absence of U.S. Food and Drug Administration (FDA) regulation or clinical data, thousands of nutraceuticals, topical consumer products, and beauty products claim benefits of hemp or cannabidiol. However, a lack of required quality control measures prevents consumers from knowing the true concentration or purities of cannabis-labeled products. Thirteen over-the-counter consumer products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Thus, in our current study, an artificial membrane, i.e., the cellulose acetate membrane representing the general biological features of the skin with desired feasibility and reproducibility [ 27 ], was selected to study the skin permeability of CBD formulations. This method was also used in a recently reported study showing that CBD's concentration and skin permeability in various cannabis-infused consumer products can be contrasting due to their formulations [ 17 ]. Thus, it is crucial to analyze the skin permeability of CBD using the IVRT assay with a cellulose acetate membrane in topical formulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in our current study, an artificial membrane, i.e., the cellulose acetate membrane representing the general biological features of the skin with desired feasibility and reproducibility [ 27 ], was selected to study the skin permeability of CBD formulations. This method was also used in a recently reported study showing that CBD's concentration and skin permeability in various cannabis-infused consumer products can be contrasting due to their formulations [ 17 ]. Thus, it is crucial to analyze the skin permeability of CBD using the IVRT assay with a cellulose acetate membrane in topical formulations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a novel formulation (a CBD-loaded O/A microemulsion microemulgel) was developed to enhance the locally acting performance of CBD for dermatological applications [ 16 ]. Additionally, a recent study analyzed the levels of CBD in several cannabis-infused consumer products, which revealed that many commercial products contain little to no detectable CBD [ 17 ]. This study also showed that CBD in these products may not penetrate the skin depending on their formulation.…”
Section: Introductionmentioning
confidence: 99%
“…The water-based CBD lotion and corresponding matrix lotion samples were prepared by weighing the lotion to the nearest 0.1 mg with a clean spatula as summarized in Tables and . , Then, 25 mL of methanol was added to the centrifuge tube, which was capped and shaken for 15 s to remove the lotion from the sides. The sample was placed in the centrifuge for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Gradient elution with mobile phases of 0.1% formic acid in water (A) and 0.1% TA B L E 1 List of the CBD vape liquids analyzed with their labeled cannabis component. formic acid in acetonitrile (B) were utilized to separate analytes and matrix components [44]. The column was maintained at a temperature of 40°C with an injection volume of 2 μL with a 10-second preand post-injection needle wash using mobile phase B.…”
Section: Lc-ms/ms Instrument Parametersmentioning
confidence: 99%